GooD4Mum: A general practice-based quality improvement collaborative for diabetes prevention in women with previous gestational diabetes. Issue 2 (April 2019) - O'Reilly, S.L.; Dunbar, J.A.; Best, J.D.; Versace, V.; Ford, D.; Young, D.; Shih, S.; Bills, R.; Shepherdley, W.; Janus, E.D.; ,
Highlights: GooD4Mum is a quality improvement study for diabetes prevention after gestational diabetes. 15 general practices in Victoria, Australia participated in GooD4Mum collaborative study. Diabetes screening rates doubled (30%–60%) and 20% increase in BMI monitoring. Improving screening and monitoring of women with previous gestational diabetes is feasible. Abstract: Aims: Gestational diabetes (GDM) and Type 2 diabetes pose tremendous health and economic burdens as worldwide incidence increases. Primary care-based systematic diabetes screening and prevention programs could be effective in women with previous GDM. GooD4Mum aimed to determine whether a Quality Improvement Collaborative (QIC) would improve postpartum diabetes screening and prevention planning in women with previous GDM in general practice. Methods: Fifteen general practices within Victoria (Australia) participated in a 12-month QIC, consisting of baseline and four quarterly audits, guideline-led workshops and Plan-Do-Study-Act feedback cycles after each audit. The primary outcome measures were the proportion of women on local GDM registers completing a diabetes screening test and a diabetes prevention planning consultation within the previous 15 months. Results: Diabetes screening increased with rates more than doubled from 26% to 61% and postpartum screening increased from 43%–60%. Diabetes prevention planning consultations did not show the same level of increase (0%–10%). The recording of body mass index improved overall (51%–69%) but the number of women with normal body mass index did not. Conclusions: GooD4Mum supported increased diabetes screening and the monitoring of high risk women with previous GDM in general practice.